Effect of Fasting On Cognitive Functioning In Healthy Young Adults - S., Shrunga M.; Shamooda, Ayisha; Shaniba, Fathimath (Journal of Health and Allied Sciences NU, 2017)
Background and objective:Cognitive flexibility refers to the ability of the brain to switch from thinking about one concept to another simultaneously. The study was taken up to evaluate the effect of fasting on Cognitive Functioning In Healthy Young Adults.Methodology: A total of 20 healthy young adults participated in the study. Paper Stroop Color Test was employed to assess inhibition and cognitive flexibility. Participants were given 4 cards (word card color card and color-word card) and were instructed to read the card as told by the clinician. The total duration taken to complete each task and incorrect responses for each task was noted. The same experiment was done in fasting and non-fasting condition for each participant.Results: The results revealed no statistical significance between the 3 tasks between 2 conditions. Though our present study did not reveal statistical significance difference between 3 tasks and 2 conditions, it was found that the performance was better during the second condition i.e. after fasting condition in comparison to first condition i.e during fasting condition.Conclusion: The study justifies these findings to be reflected due to fluid deprivation, change in life style and sleep wake up cycles with in turn effects cognitive functioning. The study also highlights on the effectiveness of stroop task in identifying the changes in cognitive function due to fasting.
Keywords: Cognition; Stroop Task; Executive Functions; Fasting